Artificial propagation, embryonic development and early larval growth of Triplophysa strauchii - Yichao Hao; Zhengwei Wang; Yinsheng Chen; Jiatao Huang; Xinyuan Ye; Jie Wei; Zhulan Nie; Jianying Xiao (Journal of Fish Biology, 2026)
Triplophysa strauchii is an endemic fish species distributed in the plateau cold‐water systems of the arid northwest region of China, playing an important ecological role in maintaining the stability of regional aquatic ecosystems. In recent years, due to human activities and habitat degradation, its wild population has been continuously declining, necessitating urgent research on artificial propagation and early development. In this study, wild mature T. strauchii from Sayram Lake were used to systematically investigate artificial propagation, embryonic development and early larval growth. Fertilized eggs were obtained using a combined domperidone (DOM) and luteinizing hormone‐releasing hormone analogue (LHRH‐A 2 ) injection protocol (8 mg/kg + 18 μg/kg for females, half dosage for males) at a water temperature of (19 ± 1)°C. The embryonic development process and larval growth from 0 to 15 days post‐hatching (dph) were continuously observed. The results showed that: (1) At a constant water temperature of (19 ± 1)°C, fertilized eggs completed hatching within 82 h, with an average hatching rate of 87.32% ± 2.16%. Embryonic development was divided into 8 stages comprising 29 developmental periods, with a total accumulated temperature of 1573.27°C ·h. By prolonging the cleavage stage (18.4%) and organogenesis stage (37.4%), the integrity and accuracy of organ differentiation under low‐temperature conditions were ensured. (2) Yolk sac absorption from 0 to 7 dph exhibited a biphasic pattern (fast–slow) and was completely absorbed by 7 days, marking the transition to exogenous nutrition. Quadratic polynomial regression models for total length, body length, head length and interorbital width against dph showed excellent fit ( R 2 >0.984), with growth rate gradually slowing with age. The relatively stable growth of head length and interorbital width reflects an adaptive strategy prioritizing the development of sensory and feeding organs. This study is the first to systematically establish an artificial propagation system for T. strauchii , clarify the timing of embryonic development and the patterns of larval growth, and fill the research gap in artificial propagation and early development of this species, providing a scientific basis and technical support for germplasm conservation, wild population restoration and large‐scale artificial breeding of T. strauchii .